Carriage of the Toxic Shock Syndrome Toxin Gene by Contemporary Community-Associated Staphylococcus aureus Isolates. (4th October 2018) - Parrish, Katelyn L; Wylie, Kristine M; Reich, Patrick J; Hogan, Patrick G; Wylie, Todd N; Kennedy, Colleen R; Lainhart, William; Hunstad, David A; Burnham, Carey-Ann D; Fritz, Stephanie A
Abstract: We report here the prevalence of the tst-1 gene among 252 methicillin-susceptible Staphylococcus aureus (MSSA) isolates and 458 methicillin-resistant S aureus (MRSA) isolates collected from 531 subjects between 2008 and 2017, one of which was recovered from a child with MRSA toxic shock syndrome. tst-1 was encoded by 43 (6%) S aureus isolates overall: 42 (16.7%) MSSA isolates and 1 (0.2%) MRSA isolate ( P < .001).